Asymptomatic Brugada Syndrome: Clinical Characterization and Long-Term Prognosis. (October 2015) - Sieira, Juan; Ciconte, Giuseppe; Conte, Giulio; Chierchia, Gian-Battista; de Asmundis, Carlo; Baltogiannis, Giannis; Di Giovanni, Giacomo; Saitoh, Yukio; Irfan, Ghazala; Casado-Arroyo, Rubén; Julià, Justo; La Meir, Mark; et al.
Abstract : Background—: Among Brugada syndrome patients, asymptomatic individuals are considered to be at the lowest risk. Nevertheless, arrhythmic events and sudden cardiac death are not negligible. Literature focused on this specific group of patients is sparse. The purpose of this study is to investigate the clinical characteristics, management, and long-term prognosis of asymptomatic Brugada syndrome patients. Methods and Results—: Patients presenting with spontaneous or drug-induced Brugada type I ECG and no symptoms at our institution were considered eligible. A total of 363 consecutive patients (200 men, 55.1%; mean age, 40.9±17.2 years; 41 [11.3%] with spontaneous type I ECG) were included. Electrophysiological study was performed in 321 (88.4%) patients, and ventricular arrhythmias were induced in 32 (10%) patients. An implantable cardioverter defibrillator was implanted in 61 (16.8%) patients. After a mean follow-up time of 73.2±58.9 months, 9 arrhythmic events occurred, accounting for an annual incidence rate of 0.5%. Event-free survival was 99.0% at 1 year, 96.2% at 5 years, and 95.4% at 10 and 15 years. Univariate analysis identified as risk factors: electrophysiological study inducibility (hazard ratio, 11.4; P <0.01), spontaneous type I (hazard ratio, 4.0; P =0.04), and previous sinus node dysfunction (hazard ratio, 8.0; 95% confidence interval, 1.0–63.9; P =0.05). At the multivariate analysis, only inducibility remained significant (hazard ratio, 9.1; P <0.01) Conclusions—: Arrhythmic events in asymptomatic Brugada syndrome patients are not insignificant. Ventricular arrhythmia inducibility, spontaneous type I ECG, and presence of sinus node dysfunction might be considered as risk factors and used to drive long-term management.